264 Harvest season, carcass weight, and fat measurement effects on lamb carcass characteristics and economic comparison of moderate and heavy weight lamb carcasses in the Western lamb processing industry. (30th November 2020) - Whaley, Jaelyn; Means, Warrie; Ritten, John; Murphy, Tom; Gifford, Cody; Cunningham, Hannah; Woodruff, Kelly; McKibben, Heather; Page, Chad M; Stewart, Whit C
Abstract: Carcass characteristics and economic impact estimates of over-finished lambs on the processing sector were evaluated in two commercial Intermountain West abattoirs. Lamb carcasses were surveyed throughout the year using digital images and imaging software (n = 9, 532). Estimations of abattoir costs and returns included loading labor, downtime cost, price of fat, live and carcass trucking costs from the two largest lamb processors in the Intermountain West. Profitability comparisons were made using Monte Carlo simulation models replicating live and carcass prices for distributions based on historical pricing data to assess overall profitability of a carcass in an ideal weight range (29.5 - 39.0 kg) and a carcass that exceeds ideal weight (> 39.0 kg). Overall means show that the average lamb carcass exceeded packer preferred hot carcass weight (40.76 ± 9.29 kg) and industry acceptable 12th rib fat thickness (8.17 ± 3.79 mm). There were seasonal differences in hot carcass weight and fat measurements with carcasses being lighter weight (P = 0.05) and trimmer (P = 0.05) in the summer months. Monte Carlo simulation found that the additional yield from heavier carcasses offset costs of harvesting them. However, factors such as machine wear and increased labor turnover rates should be considered, although difficult to quantify. Collectively, the current study shows that U.S. lamb carcasses are too heavy and excessively fat but have minor effect on processor profitability.